Failure of the Point Blinding Countermeasure Against Fault Attack in Pairing-Based Cryptography - El Mrabet, Nadia; Fouotsa, Emmanuel (Codes, Cryptology, and Information Security, 2015)
Pairings are mathematical tools that have been proven to be very useful in the construction of many cryptographic protocols. Some of these protocols are suitable for implementation on power constrained devices such as smart cards or smartphone which are subject to side channel attacks. In this paper, we analyse the efficiency of the point blinding countermeasure in pairing based cryptography against side channel attacks. In particular,we show that this countermeasure does not protect Miller’s algorithm for pairing computation against fault attack. We then give recommendation for a secure implementation of a pairing based protocol using the Miller algorithm.